Rationalisme communicationnel et rationalisme critique : la place de la philosophie habermassienne dans la pensée éducative contemporaine - Alain Firode (Nantes Université, 2021)
Contemporary pedagogues frequently base their reflections on the theory of "communicative rationalism" developed by Jürgen Habermas. Although it is rarely referred to in contemporary pedagogical literature, Karl Popper's "critical rationalism" is another attempt to restore meaning to rationalism and its values, beyond the criticism of Enlightenment universalism by twentieth-century authors. That is why the aim of this study is to confront, from the point of view of their pedagogical stakes, these two competing models of "rationalism". The final objective being, through this confrontation, to discuss some of the problems, concerning the formation of a rational mind, which arise in contemporary reflection on education.